Stability, Hydration, and Thermodynamic Properties of RNase A Confined in Surface-Functionalized SBA-15 Mesoporous Molecular Sieves - Kahse, Marie; Werner, Mayke; Zhao, Shuang; Hartmann, Martin; Buntkowsky, Gerd; Winter, Roland (Journal of Physical Chemistry C, 2014)
Mesoporous silicates (MPS) have several advantages for the immobilization of enzymes and large organic molecules. They possess well-defined pores and their surfaces can be functionalized by chemical methods. In this study, the model protein ribonuclease A (RNase A) was encapsulated in unmodified amino- and carboxy-functionalized rodlike SBA-15 with pore widths ranging from 4.0 to 5.8 nm. Differential scanning (DSC) and pressure perturbation (PPC) calorimetric techniques were employed to evaluate the stability, hydration, and volumetric properties of the confined protein. In addition, the influence of the solution pH, the surface functionalization, and cosolvents on the protein immobilization and the thermal stability of the immobilized protein are reported. The extent of stabilization depends strongly on the surface characteristics of the host, such as the charge density, and on geometric parameters, i.e., the pore size and pore volume. The addition of the chaotropic agent urea leads to an increased protein loading. Addition of the kosmotropic agent glycerol has the opposite effect. The stability of the protein RNase A confined in all the mesoporous silicates is drastically enhanced and is of the order of Delta T-m approximate to 30 + 10 degrees C regarding the increase in temperature stability. The highest immobilization capacity, fastest immobilization rate, and maximum thermal stability was achieved for the surface-functionalized SBA-15-COOH. The increased temperature stability is probably not only due to the entropy-driven excluded volume effect but also due to an increased hydration strength of the protein within the narrow silica pores, similar to the effects compatible osmolytes impose on protein hydration and stability. The absence of an expansivity increase of the confined protein after thermal denaturation indicates that inside the pores complete unfolding of the protein is not feasible anymore.